2001
DOI: 10.4009/jsdt.34.1121
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Dialysis Treatment in Japan.

Abstract: protein catabolic rate of less than 0.9g/kg/day or more than 1.5g/kg/day, and a low creatinine generation rate were risk factors in the 6-year mid-term prognosis for hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 0 publications
2
32
1
Order By: Relevance
“…15 The percentage of patients with diabetic nephropathy in the KAREN Study was similar to that of the Japanese Society for Dialysis Therapy (JSDT) Survey. 1 However, the proportion of patients with chronic glomerulonephritis in the KAREN Study was lower, and the percentage of patients with hypertensive nephrosclerosis in the KAREN Study was higher, than those in the JSDT Survey. 1 In the current study, we identified causes of ESRD using information from medical records.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…15 The percentage of patients with diabetic nephropathy in the KAREN Study was similar to that of the Japanese Society for Dialysis Therapy (JSDT) Survey. 1 However, the proportion of patients with chronic glomerulonephritis in the KAREN Study was lower, and the percentage of patients with hypertensive nephrosclerosis in the KAREN Study was higher, than those in the JSDT Survey. 1 In the current study, we identified causes of ESRD using information from medical records.…”
mentioning
confidence: 93%
“…1 However, the proportion of patients with chronic glomerulonephritis in the KAREN Study was lower, and the percentage of patients with hypertensive nephrosclerosis in the KAREN Study was higher, than those in the JSDT Survey. 1 In the current study, we identified causes of ESRD using information from medical records. The most common reason for classifying patients as unknown etiology was insufficient information regarding whether onset of proteinuria preceded that of hypertension.…”
mentioning
confidence: 93%
“…Study of the United States Renal Disease System (USRDS) and European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) registries shows that the prevalence of diagnosed Fabry disease in ESRDpatients is 0.0167% and 0.0188%, respectively (7,8). Fabry disease was not reported as the primary disease for those who initiated dialysis therapy in 1999 in the annual overview issued by the Japanese Society of Dialysis Therapy (9). However, the primary disorder for 4, 1 85 of 30,438 Japanese patients who initiated dialysis therapy in 1 999 is not specified (9).…”
Section: Discussionmentioning
confidence: 99%
“…Fabry disease was not reported as the primary disease for those who initiated dialysis therapy in 1999 in the annual overview issued by the Japanese Society of Dialysis Therapy (9). However, the primary disorder for 4, 1 85 of 30,438 Japanese patients who initiated dialysis therapy in 1 999 is not specified (9). Furthermore, a recent Japanese regional study demonstrated that 6 of 5 14 (1.2%) male chronic hemodi-Fabry Disease with Few Clinical Symptoms alysis patients were enzymatically diagnosed as having Fabry disease (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the hazard ratio (RR) for death was reduced by 23% when treatment time was increased to 4.5-4.9 h/session as compared to the reference treatment time 4.0-4.4 h/session. In Japan, treatment time longer than 4.5 h was associated with reduced RR death up to approximately 6 h and short dialysis times increased the risk of death over the reference of 4.5 h [5] . The recent DOPPS report showed that Europe and Japan have significantly longer (p !…”
mentioning
confidence: 99%